2018
DOI: 10.1016/j.jtcvs.2017.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Root replacement in acute dissection type A—A superior procedure?

Abstract: Primary root replacement repeatedly has been proposed for acute aortic dissection. Nonetheless, the need for reoperation after lessinvasive root procedures is low, at least over a 10-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…These instances require more aggressive primary surgery, such as root replacement. 26 This is a generally accepted strategy for connective…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These instances require more aggressive primary surgery, such as root replacement. 26 This is a generally accepted strategy for connective…”
Section: Discussionmentioning
confidence: 99%
“…These instances require more aggressive primary surgery, such as root replacement. 26 This is a generally accepted strategy for connective tissue disease, such as Marfan's syndrome 27 ; it may also apply to patients with preexistent root dilatation. 8 In these cases, primary aortic root replacement appears reasonable to decrease the potential risk of future proximal reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…The debate about the optimal approach to addressing the root in ATAD is analogous to the debate about arch extent. The conservative approach (root repair with reapproximation of the aortic wall, valve resuspension, and reconstruction of the sinotubular junction) is the most expeditious and reproducible in inexperienced hands but is least durable in the long-term (67,68). High volume centers have demonstrated that root replacement with prosthetic valve and valve sparing root replacement can safely be performed with excellent long-term outcomes (69)(70)(71)(72).…”
Section: Arch Extent and Proximal Repairmentioning
confidence: 99%
“…Proponents of aortic repair suggest that hospital mortality is of paramount importance and hence a more conservative repair may be preferrable in most cases. 4,17 However, it is increasingly been shown that more extensive root replacement techniques do not increase the risk of early mortality. [18][19][20][21] However, it must be borne in mind that most of these series are reported from high-volume centers and whether the results seen in these studies are reproducible at all institutions remain questionable.…”
mentioning
confidence: 99%
“…If it leads to a more durable repair, can increased early mortality be an acceptable trade‐off? Proponents of aortic repair suggest that hospital mortality is of paramount importance and hence a more conservative repair may be preferrable in most cases 4,17 . However, it is increasingly been shown that more extensive root replacement techniques do not increase the risk of early mortality 18–21 .…”
mentioning
confidence: 99%